Mubadalah and Sexual Consent Education: Bridging Religious Norms & Legal Perspective on Sexual Violence Prevention - Firdaus, Slamet; Gumiandari, Septi; Fitriana; Nafi’a, Ilman (JURNAL PENELITIAN, 2024)
Misconceptions surrounding sexual consent often serve as a catalyst for sexual violence. The absence of explicit refusal in a sexual encounter does not necessarily indicate agreement. The debate over sexual consent education has gained prominence, particularly in the context of Indonesia’s Draft Law on the Prevention and Handling of Sexual Violence (RUU PKS). This study critically examines polarized perspectives on this issue using a qualitative approach and the Mubādalah framework to find common ground. The findings reveal two opposing positions. The Institute for Criminal Justice Reform (ICJR) emphasizes that the absence of consent is a primary cause of sexual violence, advocating for sexual consent education as a preventive measure. In contrast, the Indonesian Family Love Alliance (AILA Indonesia) argues that such education contradicts Indonesia’s cultural and religious values, potentially fostering sexual permissiveness. AILA proposes a preventive approach rooted in local norms and values. The Mubādalah perspective provides a mediating lens, emphasizing that sexual activities outside marriage are impermissible in Islam. It reframes sexual consent within marital contexts and advocates education that prioritizes respect, mutual consent, and adherence to ethical and religious principles. This balanced approach addresses both ICJR’s and AILA’s concerns, fostering a culture of respect and responsibility while upholding religious values to prevent sexual violence.